Does weightlifting increase residual force enhancement? - Siebert, T.; Kurch, D.; Blickhan, R.; Stutzig, N. (Journal of Biomechanics, 2016)
The force maintained following stretching of an active muscle exceeds the isometric force at the same muscle length. This residual force enhancement (RFE) is different for various muscles. It is currently unknown whether training induces changes in RFE. Weightlifters perform a large number of eccentric contractions during training, and RFE might be functionally relevant. The aim of this study was to examine whether there is increased RFE in weightlifters versus a reference group. Therefore, we measured external reaction forces during a multi-joint leg extension in weightlifters (n=10) and a reference group (n=11) using a motor driven leg press dynamometer (ISOMED 2000). Steady state isometric forces after stretching were compared to the corresponding forces obtained during isometric reference contractions. Statistical analyses yielded a significant RFE for both groups (p<0.001), but there were no RFE differences between the groups (p=0.320). However, RFE tends to decrease slower in the weightlifting group versus the reference group. We conclude that long-term weightlifting has only a minor influence on RFE. We speculate that the specific training including a combination of eccentric and concentric exercises induced almost no changes in titin-isoform expression which may be responsible for generation of RFE after active muscle stretching.